The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1164/ajrccm.149.1.8111601
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II alleles in isocyanate-induced asthma.

Abstract: Studying genetic factors that control human immune responsiveness may further our understanding of specific types of asthma in which the role of immune factors is uncertain to date. HLA Class II gene products are involved in the control of immune responses. Therefore, we investigated whether HLA Class II genetic markers contribute to susceptibility or resistance to isocyanate-induced asthma (IAA) in exposed workers. We collected venous blood samples from two groups of unrelated white adults: (1) patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(93 citation statements)
references
References 20 publications
7
86
0
Order By: Relevance
“…In workers with exposure to diisocyanates, HLA-DQB1*0503 and DQB1*0201/0301 alleles are associated with asthma, whereas HLA-DQB1*O501 and DQA1*0101-DQB1*0501-DR1 appear to be protective (29). The alleles, HLA-DQB1*0503 and HLA-DQB1*0501, differ at residue 57 for a single amino acid, aspartic acid in DQB1*0503 and valine in DQB1*0501, suggesting that residue 57 may be a potentially critical location in the development of asthma (30).…”
Section: Pathogenesis/mechanismsmentioning
confidence: 98%
“…In workers with exposure to diisocyanates, HLA-DQB1*0503 and DQB1*0201/0301 alleles are associated with asthma, whereas HLA-DQB1*O501 and DQA1*0101-DQB1*0501-DR1 appear to be protective (29). The alleles, HLA-DQB1*0503 and HLA-DQB1*0501, differ at residue 57 for a single amino acid, aspartic acid in DQB1*0503 and valine in DQB1*0501, suggesting that residue 57 may be a potentially critical location in the development of asthma (30).…”
Section: Pathogenesis/mechanismsmentioning
confidence: 98%
“…Unlike other risk factors for biphasic reactions (that include more rapid onset of anaphylaxis delayed use of epinephrine, low doses of epinephrine, etc), mast cell diseases have never been studied as such. 4 We describe 2 patients with intraoperative anaphylaxis who were diagnosed postoperatively as having mastocytosis.…”
Section: Mast Cell Diseases and The Severity And Course Of Intraoperamentioning
confidence: 99%
“…3 For TDI-OA, the pathogenic mechanism is unknown, and there have been several reports on the genetic susceptibility of Italian 4,5,7 and Korean 6 populations.…”
mentioning
confidence: 99%
“…Bernstein et al 50) reported evidence that the involvement of the TCR Vβ repertoire expression increased the expression Vβ1 and Vβ5 after in vitro stimulation in patients who were exposed to diisocyanate. Bignon et al 51) , Balboni et al 52) and Mapp et al 53) studied the HLA class II alleles' contribution to susceptibility or resistance to isocyanate-induced asthma in exposed workers. They reported that allele DQB1*0503 and the allele combination DQB1*0201/0301 were associated with susceptibility to the disease.…”
Section: Immunological Mechanisms and Clinical Responsesmentioning
confidence: 99%